ANTECEDENTS OF THE PERFORMANCE OF SMALL AND MEDIUM - SIZED ENTERPRISE ENTREPRENEURS - Horthamarat, Chaiwat; Jamjumrus, Tawee; Chandarasorn, Voradej (Journal of Buddhist Anthropology, 2021)
The objectives of this research were to study: 1) to study the level of performance Operator qualifications Leadership skills Supply chain management And a competitive advantage of SMEs 2) to study the influence of the operator’s qualifications Leadership skills Supply chain management And competitive advantages on the performance of SMEs 3) To study ways to make the performance more efficient. And errors that cause loss of performance or dissolve business. This research employed a mixed research methodology combining quantitative and qualitative methods. In the quantitative research part, the research sample consisted of 340 SME entrepreneurs in the manufacturing sector in Bangkok. Data were collected with the use of a questionnaire. The sample size was determined based on the criterion of 20 times the observed variables. They were selected via stratified sampling and analyzed with a structural equation model. As for the qualitative research component, in-depth Collect data from Key information providers in 3 groups: 1) SMEs Operating at a loss until having to dissolve the business 2) SMEs operating for more than 5 years and 3) SMEs not less than 3 years, with a total of 4 persons per group, totaling 12 persons. The data were then analyzed with content analysis. The research findings showed that:1) performance were all rated at a high level; 2) entrepreneurs’ qualifications had the highest overall influence on the performance of SME entrepreneurs, followed by supply chain management, leadership skills, and competitive advantage, respectively; and 3) the guidelines to enhance the performance included promoting employee participation, retaining existing customers and acquiring new customers, monitoring, evaluating, and improving mistakes, and adjusting the business in corresponding to social and economic conditions. As for the mistakes that caused business loss or business dissolution, these included lack of personnel who had knowledge and capabilities to work, lack of an ability in reducing costs, lack of new customers, and high dependence on the government sector.